2017
DOI: 10.1007/s11255-017-1598-7
|View full text |Cite
|
Sign up to set email alerts
|

Close correlation between the ankle-brachial index and symptoms of depression in hemodialysis patients

Abstract: BackgroundAs both of peripheral arterial disease (PAD) and depression carried a poor prognosis in patients on maintenance hemodialysis (MHD), we investigated the correlation between the ankle-brachial index (ABI), an indicator of subclinical PAD, and symptoms of depression in patients on MHD.MethodsOne hundred and twenty-nine patients on MHD (75 males and 54 females, mean age 64.8 ± 12 years) were enrolled in this cross-sectional study, which aimed at evaluating the relationship between symptoms of depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…We only found an association between albumin levels and depressive symptoms in older adults (aged 45 years). This is actually consistent with many of the previous studies reporting a significant association, since samples investigated mainly have had mean age of >40 years [10,[12][13][14][15][16][17][18][19][20][21][22]43], while studies on samples aged <40 years predominantly did not observe any significant association between albumin and depressive symptoms [24][25][26][27].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We only found an association between albumin levels and depressive symptoms in older adults (aged 45 years). This is actually consistent with many of the previous studies reporting a significant association, since samples investigated mainly have had mean age of >40 years [10,[12][13][14][15][16][17][18][19][20][21][22]43], while studies on samples aged <40 years predominantly did not observe any significant association between albumin and depressive symptoms [24][25][26][27].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the low albumin levels could be a result of depression with inflammatory markers. However, according to some works, the correlation between lower serum albumin and depressive symptoms were independent of immunological markers like CRP and IL-6 [14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Hypoalbuminemia is a marker of poor prognosis in HD patients, being associated with depression, poor outcomes and higher mortality. 22,23 In our study, we observed that patients with serum albumin levels o 3.8 g/dL were twice as likely to be depressed. Low levels of serum albumin may reflect malnutrition, which is a risk factor for depression in older people.…”
Section: Discussionmentioning
confidence: 47%